OBSTACLES TO THE APPLICATION OF TOTAL QUALITY MANAGEMENT (TQM) IN HIGHER EDUCATION INSTITUTIONS IN THE STATE OF KUWAIT - Al Tasheh, Ghnaim Hmoud (European Scientific Journal, ESJ, 2013)
The aim of this study is introducing the obstacles of the total quality management (TQM) application in higher education institutions in Kuwait. To achieve the aim of this study , interviews were conducted with (20) members of the academic leaders in higher education institutions in Kuwait. After collecting the needed data and information, many obstacles were found out , namely: the lack of an integrated sample for the total quality management in higher education institutions, the lack of support and commitment of top leaders in higher education institutions in TQM, the lack of highly qualified professionals in the field of quality in higher education, the lack of knowledge of self-assessment mechanisms, the lack of knowledge of continuous improvement methods, the large burden on the TQM application, and the difficulty of self-assessment. The study has come out with a set of recommendations including: To set a sample for the TQM application in higher education institutions of Kuwait, holding training courses and workshops in the field of TQM application in higher education institutions and continuous improvement and self-assessment.